2016
DOI: 10.1177/1541344616655888
|View full text |Cite
|
Sign up to set email alerts
|

The Case of Educational Peacebuilding Inside the United Nations Universities

Abstract: This article examines higher education for peace inside the United Nations (UN). It offers an overview and synthesis of core concepts, organizing frameworks and theoretical premises in the field of peace and conflict studies (PACS) higher education and in the UN universities in particular, as the field aspires toward transformative learning and social justice. The article then critically analyzes the ways in which the field might perpetuate structural and cultural violence and offers implications for the UN un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 53 publications
0
10
0
2
Order By: Relevance
“…Omeje (2015) posits that “conflict-sensitive higher education” must be flexible, context-specific, participatory, and stakeholder centered when engaging in broad curriculum revision to include peace; this model asserts that peace is knowable, learnable, and teachable at the tertiary level (p. 41). However, Kester (2017) suggests that higher education for peace via curriculum, pedagogy, and instructor roles in peace education at United Nations universities is problematic; he posits a critique of the centrality of the state in such programs, the use of instruction models that silence and disadvantage certain learners, and the focus on the individual as the basis of social change. This continues to suggest that peace is the work of curriculum, teaching, and learning, not necessarily the function of the university as a whole.…”
Section: Introductionmentioning
confidence: 99%
“…Omeje (2015) posits that “conflict-sensitive higher education” must be flexible, context-specific, participatory, and stakeholder centered when engaging in broad curriculum revision to include peace; this model asserts that peace is knowable, learnable, and teachable at the tertiary level (p. 41). However, Kester (2017) suggests that higher education for peace via curriculum, pedagogy, and instructor roles in peace education at United Nations universities is problematic; he posits a critique of the centrality of the state in such programs, the use of instruction models that silence and disadvantage certain learners, and the focus on the individual as the basis of social change. This continues to suggest that peace is the work of curriculum, teaching, and learning, not necessarily the function of the university as a whole.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Saleem (2017) have opinion that for the transformation of any situation the fundamental elements are linked with the social inter consistency, after that Arif (2020) also added the same view in term of students' attitudes are result of social and religious thinking and the reason of intolerance found in the base line of unethical practices, these practice received from unreliable sources and caused of frustration and disturbed the social equilibrium of the overall community. Moreover, Tajik (2015) and Kester (2017) have opinion that role of civil society and United Nations also doing their tremendous efforts for the promotion of peace building and transform the university culture into harmony and with positive attributes. Furthermore, Halai & Durrani(2018) observed that teachers are the agents of peace, their efforts and skillful teachings develop the social cohesion in the universities of Pakistan.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The UN has been involved in international peace, security, development, and education projects since 1945, so one might consider it inevitable for this world body to establish universities to promote peace and security objectives (Coleman and Jones 2005;Muller and Roche 1995;Kester 2016). The universities of the UN, however, did not emerge until many years after the foundation of the UN organization (Salam 1973;Newland 1984;Brenes 1994;Borel et al 2011).…”
Section: Literature and Educational Contextmentioning
confidence: 99%